Analysis of thermal mixing in circle shaped body inserted inclined channel - Kok, Beşir; Varol, Yasin; Öztop, Hakan Fehmi; Koca, Ahmet (My University, 2015)
In this study, thermal mixing (TM) phenomena in a rectangle channel with adiabatic circle shaped body are investigated experimentally. Two parallel jets in different temperatures are located in the channel which has a circular exit hole to supply continuity of mass. Experiments are carried out for different inclination angle of the channel. Also, effects of ratio of flow rate, jets diameters, and temperature difference between hot and cold jets were analyzed. A circle shaped passive element with low thermal conductivity is located into channel to control thermal mixing. Thermal mixing index is calculated from measured temperatures. Experimental results showed that thermal mixing of fluid is effected from geometric parameters, drastically. It is found that TM is function of the temperature difference of inlet jets.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Isıl Karışım; Paralel Jet; Isı Transferi